Induced ferromagnetic behavior of Cr doped ZnS nano particles. (2022) - Manivannan, N.; Chandar Shekar, B.; Matheswaran, P.; Mohammed Ibrahim, M.; Senthil Kumaran, C.K.
Abstract: Cr ions doped with Zinc sulphide nanoparticles were synthesised by chemical route and studied their structural, morphology and magnetic properties. Predominant peaks of XRD shifted towards higher angle with dopant concentration which were corresponds to the structural deformation in the presence of Cr ions. SEM images for different dopants concentration showed high difference in morphology. Presence of Zn, S and Cr were confirmed by EDAX spectra. HRTEM images revealed that formation of NPs and nano crystalline nature of Cr doped ZnS . The results from selected area electron diffraction pattern (SAED) was good agreement with the XRD results. Ferromagnetism was observed for Cr doped ZnS NPs. RFM enhanced with increasing dopants concentration.